2022
DOI: 10.36681/tused.2022.108
|View full text |Cite
|
Sign up to set email alerts
|

Developing of a problem solving essay test ınstrument (PSETI) in an ınstruction of basic science concepts in ethno science context for preservice elementary school teachers

Abstract: Assessment of problem-solving skills for preservice teachers is important in science instruction. The purpose of this study is to discover; (a) How are the characteristics of the Problem-Solving Essay Test Instrument (PSETI); (b) How is the validity based on experts assessment; (c) how are the validity and reliability based on trials. The research method is research and development. The study covers three stages, those are (1) planning the test, (2) trying out the test, (3) determining the validity, and the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Accordingly, it is important to pay attention to the integration of science, technology and entrepreneurship in educational programs. This is the conclusion reached by the authors of the review article Sri Jumini, Sutikno Madnasri, Edy Cahyono, P Parmin [2]. It should be noted that as part of their research, 851 articles from Google Scholar and Scopus with their metadata for 2015-2020 were included in the review, in which there was mention of scientific teaching and a number of scientific methods.…”
Section: Introductionmentioning
confidence: 73%
“…Accordingly, it is important to pay attention to the integration of science, technology and entrepreneurship in educational programs. This is the conclusion reached by the authors of the review article Sri Jumini, Sutikno Madnasri, Edy Cahyono, P Parmin [2]. It should be noted that as part of their research, 851 articles from Google Scholar and Scopus with their metadata for 2015-2020 were included in the review, in which there was mention of scientific teaching and a number of scientific methods.…”
Section: Introductionmentioning
confidence: 73%
“…A research and development model method was used, and the final product is a habit of mind (HoM) questionnaire instrument in the context of basic physics practicum. Instrument development referred to 3 stages, namely (1) planning the test, (2) trying out the test, and (3) determining the validity, and reliability (Oriondo & Dallo-Antonio, 1998;Yanto et al, 2019;Aristiawan & Istiyono, 2020;Winarto et al, 2022). The flow diagram of the research and development instrument is shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…The application of ethnoscience can be applied purely or integrated with others. The pure application of ethnoscience also has a significant impact on improving students' cognitive knowledge, such as the ability to think creatively, scientific literacy, and understanding concepts (Mahyuny, Nursamsu, Hasruddin, & Muslim, 2022;Winarto, Sarwi, Cahyono, & Sumarni, 2022). Ethnoscience is authentic so that students are easier to understand science learning.…”
Section: Ethnoscience Integration In Learningmentioning
confidence: 99%